Implementation of fluid-structural interaction for finite element study on the human cochlear using openfoam - Ling, Jeremy Cheng Xun (2017)
Limited by the location of the cochlear within the skull, as well as the prior technologies, there have been limitations studying the cochlear, the mechanics behind it, and more recently, its behaviour. Over the years, the rise in technology has enabled the possibilities of studying the underlying behaviours of the cochlear by understanding its parameters. In solving most questions, problems are broken down and simplified into equations that focuses on the behaviour in different domains, and to truly understand and obtain a solution and understand, there is a need to compile and integrate the results. The fluid-structure interaction is a method that enables the study of the fluid in response to the changes in the solid structure, and vice versa. Although commercial softwares are widely available, there is a limitation for students and non-sponsored researchers due to the license covering the use of these commercial softwares.